Fatigue behavior of an ultrafine-grained metastable CrMnNi steel tested under total strain control. (January 2018) - Droste, M.; Ullrich, C.; Motylenko, M.; Fleischer, M.; Weidner, A.; Freudenberger, J.; Rafaja, D.; Biermann, H.
Highlights: Remarkable high yield strength, tensile strength, and a good ductility. Higher stress amplitude but lower cyclic hardening due to α′-martensite formation. Higher fatigue life than CG material at all tested strain amplitudes. α′-martensite nuclei form inside austenitic grains via ε-martensite. Abstract: An ultrafine-grained (UFG) microstructure in a metastable austenitic CrMnNi steel was achieved using a thermo-mechanically controlled process by rotary swaging and subsequent reversion annealing. The material with an average grain size of 0.7 μm was cyclically deformed in total strain controlled tests at strain amplitudes in the range of 0.3% ≤ Δεt /2 ≤ 1.2%. This treatment increased the cyclic stress amplitudes as well as the fatigue life in comparison with the conventionally grained counterpart. For strain amplitudes Δεt /2 ≥ 0.4% a martensitic phase transformation occurred, which was observed in situ by a ferrite sensor as an increase of the α′-martensite fraction. The microstructure changes, and the deformation mechanisms in particular, were investigated by means of electron backscatter diffraction, scanning electron microscopy in transmission mode and transmission electron microscopy that revealed the formation of small α′-nuclei which rapidly grew until the entire austenitic grain was transformed.